Involvement and regulation of the left anterior cingulate cortex in the ultrasonic communication deficits of autistic mice - Hou, Yilin; Li, Yuqian; Yang, Dingding; Zhao, Youyi; Feng, Tingwei; Zheng, Wei’an; Xian, Panpan; Liu, Xufeng; Wu, Shengxi; Wang, Yazhou (Frontiers in Behavioral Neuroscience, 2024)
Introduction: Autism spectrum disorder (ASD) is a group of diseases often exhibiting poor sociability and social communication. Anterior cingulate cortex (ACC) is a core brain region in social function. Whether it contributes to the defects of social communication of ASD and whether it could be physiologically modulated to improve social communication have been poorly investigated. This study is aimed to address these questions.Methods: Fragile X mental retardation 1 (FMR1) mutant and valproic acid (VPA)-induced ASD mice were used. Male-female social interaction was adopted to elicit ultrasonic vocalization (USV). Immunohistochemistry was used to evaluate USV-activated neurons. Optogenetic and precisely targeted transcranial magnetic stimulation (TMS) were utilized to modulate ACC neuronal activity.In wild type (WT) mice, USV elicited rapid expression of c-Fos in the excitatory neurons of left, but not right ACC. Optogenetic inhibition of left ACC neurons in WT mice effectively suppressed social-induced USV. In FMR1 -/-and VPA-induced ASD mice, significantly less c-Fos/CaMKII-positive neurons were observed in left ACC following USV, as compared with that in control. Optogenetic activation of left ACC neurons in FMR1 -/-or VPA-pretreated mice significantly increased social activity elicited USV. Further, precisely stimulating neuronal activity in left ACC, but not right ACC, by repeated TMS effectively rescued USV emission of these ASD mic.The excitatory neurons in the left ACC are responsive to social elicited USV. Their silence mediates the deficiency of social communication of FMR1 -/-and VPA-induced ASD mice. Precisely modulating left ACC neuronal activity by repeated TMS is able to promote social communication of FMR1 -/-and VPA-pretreated mice.